Novos táxons sul-americanos de Compsocerini (Coleoptera, Cerambycidae) - Napp, Dilma Solange; Martins, Ubirajara Ribeiro (Papéis Avulsos de Zoologia, 2006)
New South American taxa of Compsocerini (Coleoptera, Cerambycidae). The following new genus and species, all from Bolivia, are described in Compsocerini: Ecoporanga gen. nov., type species E. achira sp. nov., Dilocerus brunneus sp. nov., Rierguscha florida sp. nov., from Santa Cruz, and Ethemon iuba sp. nov. from Cochabamba.